Environmental protection and conservation the case of Laguna Lake and other theoretical approaches - Santos, Antonio L. (Journal of Nature Studies, 2010)
The environment provided the matrix upon which man's survival depends. One way of better understanding the environment is to take a closer look at the interplay of various stakeholders in a given situation or problem, like water pollution.